Optimization of solid waste collection system for Bangkok City, Thailand - Rangsan Pinthong; Chongrak Polprasert; Vigneswaran, Saravanamuthu; Shin, H. S.; Government of Federal Republic of Germany, IeScholarship Donor (Bangkok : Asian Institute of Technology, 1987)
A study was carried out to determine optimum situation for collection and transportation of solid wastes for the city of Bangkok. Models were development to quantify and analyze the relationship of the parameters of solid waste collection systems in Bangkok. The solid waste collection data was obtained from the five collection areas in Yannawa District. The parameters and variables that affect the solid waste collection systems in Bangkok were analyzed by means of statistical analysis and computer simulation model. The Collection cost and efficiency of collection were the tools for deciding the optimum situation. The load-container truck of 12 cu. m with 1 crew, using station collection method, was found to be the best system to be used in solid waste collection systems. The use of transfer station between the collection areas and the disposal site was determined to be appropriate. The Capacity and location of a transfer station were determined by Fortran Programming. The transfer station of 816 cu. m capacity could be located at 5 or 10 km far from disposal site if the distance between disposal site and collection areas was 20 km. The combination of solid waste collection Systems and transfer station system would give lesser cost than employing solid waste collection systems only.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Technology
Thesis (M.Sc.) - Asian Institute of Technology, 1987
Keywords: Refuse and refuse disposal -- Thailand -- Bangkok; Mathematical optimization